Gastric NET Subtypes: Do We Need An Additional One? - Lock, Guntram; Oelckers, Michael; Clauditz, Till Sebastian; Schrader, Jörg (Zeitschrift für Gastroenterologie, 2021)
Depending on etiology, prognosis and malignant potential, recent S2k guideline differentiates gastric neuroendocrine tumors (gNET) in 4 types with different treatment implications.We report on a 55-year-old patient with the accidental finding of a 15 mm gNET. Apart from a prolonged use of proton pump inhibitors (PPI) for 20 years as a treatment for gastroesophageal reflux disease, there were no other associations or risk factors for gNETs. Formally, this patient would have been classified as a type III gNET, implicating gastric surgery. From a pathophysiological point of view, however, the assumed prolonged gastrin hypersecretion would have justified an assignment as a type I gNET. The gNET was resected by ESD, but histology showed an R1 situation. After cessation of PPIs, there is no recurrence so far. Besides, the initially documented numerous and large gland polyps showed an impressive regression only a few weeks after cessation of PPI.This case points to a probably underestimated gap in the present gNET classification. On the basis of present literature, the therapeutic dilemma of PPI-associated gNETs is discussed. A new assignment of PPI associated gNETs as type Ib could help to overcome this dilemma.
Keywords: gastric polyp; neuroendocrine tumor; endoscopy